2009
DOI: 10.1080/09540120802537831
|View full text |Cite
|
Sign up to set email alerts
|

Community interventions providing care and support to orphans and vulnerable children: a review of evaluation evidence

Abstract: Children affected by HIV in their families and communities face multiple risks to their health, education and psychosocial wellbeing. Community interventions for children who have been orphaned or rendered vulnerable take many forms, including educational assistance, home-based care, legal protection and psychosocial support. Despite a recent influx of funding for programme implementation, there exists little evidence to inform policymakers about whether their investments are improving the lives of vulnerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 54 publications
1
52
1
Order By: Relevance
“…However, data suggest that orphans were not at greater risk of dropping out than other children. It is possible that orphanhood provides a visible indication of vulnerability which attracts support from community and organizations, the so-called "lucky orphan syndrome" (Schenk, 2009). By contrast, age was not used as a criterion for identifying the children at-risk, although our data show that older age was the most reliable predictor of both dropout and poor achievement.…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…However, data suggest that orphans were not at greater risk of dropping out than other children. It is possible that orphanhood provides a visible indication of vulnerability which attracts support from community and organizations, the so-called "lucky orphan syndrome" (Schenk, 2009). By contrast, age was not used as a criterion for identifying the children at-risk, although our data show that older age was the most reliable predictor of both dropout and poor achievement.…”
Section: Discussioncontrasting
confidence: 36%
“…Indeed, such evidence is lacking for the support of orphans and vulnerable children in general (Schenk, 2009) and yet it is critical for evidence-based policy decisions.…”
Section: Introductionmentioning
confidence: 99%
“…However, little evidence exists about what types of programs enhance the well-being of OVC. 10 We have conducted studies in Zambia to understand local mental and behavioral health problems, validate mental and behavioral assessment instruments, and examine the cross-cultural feasibility of evidence-based treatment. [11][12][13][14][15] These studies culminated in the randomized clinical trial reported in this article, which tests the effectiveness of trauma-focused cognitive behavioral therapy (TF-CBT; http://tfcbt.musc.edu/) 16 for OVC compared with treatment as usual (TAU) provided by lay counselors without previous mental health care training.…”
mentioning
confidence: 99%
“…Home visiting is a popular family-centered program approach for HIV-affected families in which care workers provide a range of support services during regular visits (Schenk, 2009; United Nations Children's Fund [UNICEF], 2010). Home visiting programs tend to be multifaceted, aiming to impact many aspects of well-being.…”
Section: Introductionmentioning
confidence: 99%